2020
DOI: 10.3390/agronomy10020275
|View full text |Cite
|
Sign up to set email alerts
|

The Multifactorial Effect of Digestate on the Availability of Soil Elements and Grain Yield and Its Mineral Profile—The Case of Maize

Abstract: The fertilizer value of digestate (a biogas plant byproduct) depends on its impact on the availability of soil nutrients and on the concentration of minerals, including heavy metals, in the edible crop parts. This hypothesis was verified in field experiments with maize conducted in the years 2014, 2015, and 2016 in Brody, Poland. The two-factorial experiment consisted of the digestate application method and its rate: 0.2, 0.4, and 0.8 t ha −1 . Maize yield in consecutive years fitted the quadratic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…More recently, the work of Przygocka-Cyna and Grzebisz [39] showed that any increase in Fe concentration in corn grain resulted in a simultaneous decrease in Cd concentration, attesting then for an antagonism behaviour between these two elements. More clearly, Przygocka-Cyna and Grzebisz [39] stated that an increased exogenous supply of Fe results in decreased uptake by plant roots.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently, the work of Przygocka-Cyna and Grzebisz [39] showed that any increase in Fe concentration in corn grain resulted in a simultaneous decrease in Cd concentration, attesting then for an antagonism behaviour between these two elements. More clearly, Przygocka-Cyna and Grzebisz [39] stated that an increased exogenous supply of Fe results in decreased uptake by plant roots.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, the work of Przygocka-Cyna and Grzebisz [39] showed that any increase in Fe concentration in corn grain resulted in a simultaneous decrease in Cd concentration, attesting then for an antagonism behaviour between these two elements. More clearly, Przygocka-Cyna and Grzebisz [39] stated that an increased exogenous supply of Fe results in decreased uptake by plant roots. And this indeed the case with our experiments, where the concentration of Fe was significantly augmented in both cleaned biosolids by 13% to 20% as this metal is added (as ferric chloride) to biosolid during the application of the leaching process [28].…”
Section: Discussionmentioning
confidence: 98%
“…It seems that, with the addition of chemical fertilizer to the soil, soil nitrogen increased. Consequently, the plant's uptake of this element increased, and with its transfer to the grain, the percentage of grain nitrogen increased [45]. Mulyani et al [46] reported that the combination of chemical fertilizers increased the uptake of nitrogen, phosphorus, and potassium in sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the work of Przygocka-Cyna and Grzebisz [41] showed that any increase in Fe concentration in corn grain resulted in a simultaneous decrease in Cd concentration, attesting to an antagonistic behaviour between these two elements. In fact, Przygocka-Cyna and Grzebisz [41] stated that an increased exogenous supply of Fe results in decreased uptake by plant roots.…”
Section: Lixiviation Of Metals Through Leachatementioning
confidence: 99%